Beyond order 12 more rules for life - Dr. Jordan B. Peterson ([New York, New York] Penguin / Portfolio, 2021)
n 12 Rules for Life, clinical psychologist and celebrated professor at Harvard and the University of Toronto Dr. Jordan B. Peterson helped millions impose order on the chaos of their lives. Now, in this bold sequel, Peterson delivers 12 more lifesaving principles for resisting the exhausting toll that our desire to order the world inevitably takes.
Includes bibliographical references and index.
Keywords: Conduct of life